(untitled) (Research, Society and Development, 2025)
Excessive screen time has become a growing concern in contemporary society. With the widespread use of electronic devices such as smartphones, tablets, and computers, people spend more and more time in front of screens. The objective of this study was to provide a critical and informed view of the effectiveness of proposed interventions to reduce screen time in children and adolescents. The systematic literature review was conducted between August and December 2023. A high-sensitivity search was conducted in the Medline database via PubMed, initially finding 349 articles. After applying the inclusion and exclusion criteria, six articles remained for analysis, followed by data extraction and bias assessment. The studies were examined for risk of bias, with some classified as high risk and others lacking sufficient information (unclear bias), raising doubts about their reliability. Considering the studies included to assess the impact of screen time on the lives of children and adolescents, it was observed that most used different interventions, generating varying primary outcomes. This heterogeneity compromised direct comparisons between results. Therefore, it is necessary to create a standardized, validated, and legitimized protocol that provides consistent and sustainable results in reducing screen time, ensuring effective benefits to health and well-being. Such standardization would allow for greater comparability across studies, favoring the construction of solid evidence through new systematic literature reviews.